The history of mathematics : - Burton, David M. (McGraw Hill, 2007)
This text concentrates on the history of those topics typically covered in an undergraduate curriculum or in secondary schools. It presents a full account of how mathematics has developed over the last 5000 years, and assorted problems of varying degrees of difficulty have been interspersed throughout the text.